A 4 U laser heterodyne radiometer for methane (CH4) and carbon dioxide (CO2) measurements from an occultation-viewing CubeSat. (13th January 2017) - Wilson, Emily L; DiGregorio, A J; Riot, Vincent J; Ammons, Mark S; Bruner, William W; Carter, Darrell; Mao, Jianping; Ramanathan, Anand; Strahan, Susan E; Oman, Luke D; Hoffman, Christine; Garner, Richard M
Abstract: We present a design for a 4 U (20 cm × 20 cm × 10 cm) occultation-viewing laser heterodyne radiometer (LHR) that measures methane (CH4 ), carbon dioxide (CO2 ) and water vapor (H2 O) in the limb that is designed for deployment on a 6 U CubeSat. The LHR design collects sunlight that has undergone absorption by the trace gas and mixes it with a distributive feedback (DFB) laser centered at 1640 nm that scans across CO2, CH4, and H2 O absorption features. Upper troposphere/lower stratosphere measurements of these gases provide key inputs to stratospheric circulation models: measuring stratospheric circulation and its variability is essential for projecting how climate change will affect stratospheric ozone.